2017
DOI: 10.1097/fpc.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient perceptions of genomic testing to inform pharmacogenomic implementation

Abstract: OBJECTIVE Pharmacogenomics seeks to improve prescribing by reducing drug inefficacy/toxicity. However, views of patients during pharmacogenomic-guided care are largely unknown. We sought to understand attitudes and perceptions of patients in an institutional implementation project and hypothesized that views would differ based on experience with pharmacogenomic-guided care. METHODS Two focus groups were conducted–one group consisted of patients who had previously submitted to broad pharmacogenomic genotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…In addition, five large healthcare system–based pharmacogenetics implementation projects of multigene panels, including SLCO1B1 , have reported preliminary or final results: four in the United States (1,200 Patients Project; INdiana GENomics Implementation: an Opportunity for the UnderServed (INGENIOUS); the Marshfield Clinic; and the RIGHT protocol) and one from La Paz University Hospital in Spain ( Table ). Most of these projects are using passive or active CDS in the EHR to support prescriber use of pharmacogenetic results in several different clinically actionable pharmacogenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, five large healthcare system–based pharmacogenetics implementation projects of multigene panels, including SLCO1B1 , have reported preliminary or final results: four in the United States (1,200 Patients Project; INdiana GENomics Implementation: an Opportunity for the UnderServed (INGENIOUS); the Marshfield Clinic; and the RIGHT protocol) and one from La Paz University Hospital in Spain ( Table ). Most of these projects are using passive or active CDS in the EHR to support prescriber use of pharmacogenetic results in several different clinically actionable pharmacogenes.…”
Section: Resultsmentioning
confidence: 99%
“…The study was powered to detect a one-point difference in the primary outcome of a medication adherence scale; secondary outcomes included low-density lipoprotein cholesterol (LDL-C) at 3 and 8 months, the Brief Pain Inventory, and the Short Form Health Survey quality-of-life measure. 42,43 In addition, five large healthcare system-based pharmacogenetics implementation projects of multigene panels, including SLCO1B1, have reported preliminary or final results: four in the United States (1,200 Patients Project 11,(44)(45)(46)(47)(48)(49) ; INdiana GENomics Implementation: an Opportunity for the UnderServed (INGENIOUS) 13,50,51 ; the Marshfield Clinic 12,52 ; and the RIGHT protocol 8,11,12,[53][54][55][56] ) and one from La Paz University Hospital in Spain 10 ( Table 1). Most of these projects are using passive or active CDS in the EHR to support prescriber use of pharmacogenetic results in several different clinically actionable pharmacogenes.…”
Section: Search Resultsmentioning
confidence: 99%
“…Participants in a focus group study on patient, physician, and pharmacist opinions on PGx conducted by Frigon et al [15] commented on the potential for PGx test results to limit the experience of having a physician discount a patient's report of a drug side-effect as a "psychosomatic" event rather than a real drug side effect. The notion of PGx results potentially leading people to conclude that any and all adverse events from a drug was due to their genetic make-up was noted by Lee et al [16] in their focus group study comparing the attitudes and perceptions of individuals exposed to PGx-guided care versus those of individuals with traditional care. On the other hand, some studies have found that individuals receiving PGx test results may be more medication compliant and willing to tolerate some side effects if PGx testing was utilized to assist with drug and dose selection [2,16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants requesting genetic counseling (54%) were seeking general assistance with understanding their PGx result reports, often alluding to uncertainty regarding whether they should or should not take a given medication in the future based on their results. The expectation for PGx test results to have the potential to inform physician prescribing decisions in a way that maximizes drug efficacy while limiting adverse reactions has been captured in several other studies, including studies of participants who have received PGx results [2,3,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation